Factors Related To The Incidence Of Traffic Accident In Smk Kesehatan Plus Prima Mandiri Of Makassar - Rosdiana Syakur; Hanafi Abdul Kadir; Maryono Dassi; Fitri Usman (Jurnal Komunitas Kesehatan Masyarakat, 2020)
According to WHO, traffic accidents are events on road traffic that involve at least one vehicle that causes injury or damage or harm to the owner or the victim of the accident. This research aims to determine the factors related to the incidence of traffic accidents in the youth at SMK Health, Plus Prima Mandiri Makassar in 2019. This type of observational research is used with the Cross Sectional Study Draft. The sample in this study amounted to 54. Sampling using the Purposive sampling method. Data analysis of univariate and bivariate using Chi-square test. The results of the study based on sufficient analysis stated there is a driving behavior relationship with the accident incident and then Linta (p = 0.003), SIM ownership (p = 0.000), parental consent (p = 0.005). Use of the APD is not associated with the incidence of traffic accident (P = 0.742). Recommended for students not using HP while driving, students must use helmets, masks, and gloves on the drive, students who do not own the SIM to avoid riding motorcycles, and students and schoolgirls who are allowed by parents to Riding the motor so as not to be distracted while driving.